Incel Fenomeni: Psikolojik özellikler, radikalleşme ve adli yansımalar - Erk, Mehmet Aykut; Fırat, Sunay; Dokgöz, Halis (Adli Tıp Bülteni, 2025)
This study examines the psychological, sociological, and forensic dimensions of the “incel” (involuntary celibacy) subculture. Emerging from online forums, incel ideology initially served as a space for sharing loneliness and social exclusion, but gradually radicalized into a structure legitimizing misogyny, hate speech, and violence. Within the framework of the “Young Male Syndrome,” tendencies toward risk-taking, aggression, and social alienation are discussed, while emphasizing the ideology’s roots in biological determinism and partner-finding failure. Case analyses of the Tallahassee Yoga Studio attack, and the A.K. stabbing highlight the risk of online radicalization translating into real-world violence. Findings reveal that the incel phenomenon is shaped not only by individual psychopathologies but also by gender norms, digital culture, and collective frustrations. By contextualizing the phenomenon in Turkey, this study contributes to the literature and proposes multi-level (micro, meso, macro) preventive strategies for policy and practice.